The Graphic Novel Classroom : POWerful Teaching and Learning With Images. - Bakis, Maureen M. (SAGE Publications, 2011)
A secret weapon for engaging adolescents Could you use a superhero to teach reading, writing, critical thinking, and problem-solving? While seeking the answer, secondary language arts teacher Maureen Bakis discovered a powerful pedagogy that teaches those skills and more. The amazingly successful results prompted her to write this practical guide that shows how to use graphic novels to: Teach 21st-century skills, including interpretation of content and form Promote authentic literacy learning Grow learners' competency in writing and visual comprehension Motivate students to create in multiple.